2011
DOI: 10.5811/westjem.2011.2.1785
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Complications in Acute Ischemic Stroke

Abstract: Introduction: To characterize cardiac complications in acute ischemic stroke (AIS) patients admitted from an urban emergency department (ED). Methods:Retrospective cross-sectional study evaluating AIS patients admitted from the ED within 24 hours of symptom onset who also had an echocardiogram performed within 72 hours of admission.Results: Two hundred AIS patients were identified with an overall in-hospital mortality rate of 8% (n ¼ 16). In our cohort, 57 (28.5%) of 200 had an ejection fraction less than 50%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 42 publications
1
20
0
2
Order By: Relevance
“…The correlation of NSM with NIHSS scores is also remarkable. Wira et al observed that troponin levels, the presence of ischemic ECG changes, and in‐hospital mortality rates were statistically higher in patients with NIHSS scores > 10 than in patients with NIHSS scores < 10. They observed that myocardial systolic dysfunction was more pronounced in patients with high NIHSS scores, without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of NSM with NIHSS scores is also remarkable. Wira et al observed that troponin levels, the presence of ischemic ECG changes, and in‐hospital mortality rates were statistically higher in patients with NIHSS scores > 10 than in patients with NIHSS scores < 10. They observed that myocardial systolic dysfunction was more pronounced in patients with high NIHSS scores, without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…General management of AIS is often complicated because of both possible cardiovascular dysfunction and several medical complications, such as swallowing impairment, neurogenic respiratory failure, stroke-associated pneumonia, gut dysbiosis, systemic inflammation, and need for tracheostomy or mechanical ventilation [41]. The National Institutes of Health Stroke Scale/Score (NIHSS) should be used for risk stratification, given its proven utility in detecting AIS patients at high cardiovascular risk; studies have found that patients with a NIHSS > 10 have higher troponin levels and more ischemic changes when compared to those with a score < 10 [70]. Figure 6 provides a practical flowchart for the management of AIS patients at risk of cardiovascular dysfunction in the intensive care unit (ICU).…”
Section: Cardiovascular Monitoring In Patients With Overt Aismentioning
confidence: 99%
“…Neurogenic cardiomyopathy with ECG changes and left ventricular dysfunction is well documented in association with major intracranial events 27. Our patient's stroke may have caused subtle cardiomyopathy with impaired diastolic right ventricular (RV) function without systolic dysfunction of either ventricle, thus increasing the RA-to-LA pressure gradient.…”
Section: Discussionmentioning
confidence: 82%